Hubungan status pestisida dengan status gangguan akibat kekurangan yodium (GAKY) anak SD pada daerah endemik GAKY Kabupaten Dairi - Maryanes Maryanes; Wiryatun Lestariana; Untung S Widodo (Jurnal Gizi Klinik Indonesia, 2008)
Background: Thyroxin plays important role in the metabolism of carbohydrate, protein and cholesterol, and in the process of growth. Iodine deficiency disorder not only can be caused by lack of iodine substance but also another competition factor, which is a pollutant substance which is goitergenic (pesticide). This goitergenic substance interferes hormonogenesis of thyroid causing enlargement of thyroid gland known as goiter.Objective: This study was aimed at examining the relationship between status of pesticide and status of iodine deficiency disorders (urinary iodine excretion) of elementary school children and the difference between them based on level of their endemic in Dairi District.Methods: This was an observational study using a cross-sectional design. Palpation of thyroid gland was made to determine the level of endemic; concentration of blood cholinesterase was determined using tinto meter kit; urinary iodine excretion was analyzed with the ammonium persulfate digestion method. Data was analyzed with chi square and anova.Results: Chi square test indicated that the relationship between the concentration of blood cholinesterase and urinary iodine excretion was significant (p<0.05) with OR 11.1 and the relationship between concentration of cholinesterase and iodine deficiency disorders (palpation) was not significant (p>0.05) with OR 1.3. Anova test, based on endemic, indicated that there was a significant difference between the concentration of blood cholinesterase and urinary iodine excretion (p<0.05).Conclusion: There was significant relationship between status of pesticide (concentration of blood cholinesterase) and status of iodine deficiency disorder based on urinary iodine excretion and there was no significant relationship between concentration of cholinesterase and iodine deficiency disorders based on the result of palpation. There was a difference in the average status of pesticide and iodine deficiency disorders status among the elementary school children based on their endemic.